Intimidação sistemática (bullyng) em escolas estaduais de Medianeira-PR: políticas públicas e ações - Franco, Liane Maria Gonçalves (2021)
This research entitled "Systematic Intimidation (Bullying) in state schools of Medianeira: public policies and actions" presents considerations about the forms of violent manifestation associated with the practice of bullying in state schools in the Municipality of Medianeira, located in the western region of the state of Paraná. On September 28, 2018, a 15-year-old teenager entered School João Manoel Mondrone State High School with a gun and shot at classmates, an event that touched the entire community. What fact would have motivated this action? This questioning and the attack that took place in this city caused inquietude and stimulus for this master's research. That said, the scope was to get to know and present the strategic actions that five State Schools in Medianeira (PR) have carried out in their projects to prevent and face systematic intimidation (bullying). The methodology was qualitative, using as basic tools semi-structured interviews and questionnaires, applied to principals, educators, and students from the selected schools. The theoretical foundation is based on the studies of Fante (2005), Antunes and Zuin (2008), and Crochick and Crochick (2017), in addition to official documents based on Laws No. 17.355/2012, No. 13.185/2015, No. 13.663/2018, and other guiding instructions of the pedagogical work related to the theme. The development of the research made it possible to understand that, unfortunately, in all schools, bullying practices have already occurred, however, no institution have left to look for solutions to these occurrences. There is the implementation of projects guided by the State Department of Education (SDE), with actions aimed at combating systematic bullying. From this legal support, the schools provide assistance to the victims, the aggressors, and the family, and then, together with the school community, seek strategies to minimize the problem and reduce the existing violence rates.